A study on the development, operation & potential of paging service industry / Aminuddin Ghazali ... [et_al.] - Ghazali, Aminuddin; Hashim, Amran; Abd. Aziz, Mohd Farris; Sukaimi, Muhammad Noor; Yahaya, Razhan (1987)
This report briefly describes the development of the paging industry in Kuala Lumpur. The report traces the beginning of paging service in Malaysia in 1974, the events and changers that took place in the industry and the present situation. A comprehensive, study of the organizations involved in paging service industry revealed the complexities and problems of operating the service. There are different types, of operation system depending on the type of equipment used, and each system has its own advantages and disadvantages. This report also describes the service rate, price of pagers, subscribers and marketing strategies. Two surveys were made to find out the opinion and response of subscribers and public towards the paging service. The public are tested in terms of their awareness, and perception towards the service. The subscribers are tested in terms of their satisfaction towards the service. This report also touch upon the potential of the paging industry in terms of the market ability to grow further advancement of technology, wider and more varied service and playing a significant role in increasing productivity.